EVALUATION OF RELATION BETWEEN ADITUS PATENCY AND DEGREE OF HEARING LOSS IN TUBOTYMPANIC CSOM: ORIGINAL ARTICLE - MOHAMMAD SAJJAD ZAHIR; DR. CHANDRA BHAN; DR. PRAMOD KUMAR YADAV; DR. SUSHIL KUMAR SHARMA (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Chronic suppurative otitis media is defined as a chronic infection of the mucoperiosteal lining the middle ear cleft. Middle ear cleft includes the eustachian tube, hypotympanum, mesotympanum, epitympanum, aditus and mastoid air cell system. Upper part of middle ear has an important opening known as the aditus ad antrum. Which communicates the epitympanic recess with the mastoid antrum. It is very important for the aeration of the mastoid air cells. Studies show that obstruction of the aditus ad antrum is related with pathogenesis of CSOM. In tubotympanic type of CSOM obstruction of aditus occurs most commonly with granulation tissue, edematous mucosa, tympanosclerosis and rarely with mucous membrane. Aim of our study is to check the aditus patency in tubotympanic type CSOM having dry ear, central perforation, middle ear mucosa healthy in mild and moderate hearing loss.